PERAN PENYULUH PERTANIAN PADA KELOMPOK TANI DI DESA KANONANG EMPAT KECAMATAN KAWANGKOAN BARAT KABUPATEN MINAHASA (The Role Of Agricultural Extension Workers in Kanonang Empat Village, West Kawangkoan Sub District, Minahasa Regency) - Yeremia David Rumimper; Celsius Talumingan; Sherly G. Jocom (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
The objective of this research is to determine the role of agricultural extension workers in Kanonang Empat Village, West Kawangkoan Sub District, Minahasa Regency. The data used in this study are primary and secondary data. Sampling technique in this study with purposive sampling technique. The number of sample farmer groups is 2 groups of respondents, Torona and Kompas with each having 20 members. Data collection methods are observation, interview and documentation methods. Variable levels of the role of the extension worker that were measured were the role of the extensionist as a motivator, the role of the extensionist as an educator, the role of the extensionist as a catalyst, the role of the extensionist as an organizer, the role of the extensionist as a communicator and the role of the extensionist as an adviser. Rolelevel variables are measured using a Likert scale. The research results showed that the role of agricultural extension workers in the Torona and Kompas farmer groups was very instrumental, both in their roles as motivators, educators, catalysts, organizers, communicators with the role scores obtained ranging from 264 to 271 and their roles as advisors with scores obtained ranging from 177 and 179. Played a big role in this because the extension workers had provided counseling materials according to the farmer's requests, were on time in conducting counseling, had a good attitude, and prioritized farmer groups in Kanonang Empat Village in terms of distributing aid and information.